2020
DOI: 10.1016/j.biortech.2020.123099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incubation conditions on protein and C-Phycocyanin recovery from Arthrospira platensis post- pulsed electric field treatment

Abstract: Pulsed electric field (PEF) was conducted for the extraction of proteins/C-Phycocyanins from Arthrospira platensis. The cyanobacterial suspension was treated with 1 µs long pulses at an electric field strength of 40 kV•cm-1 and a treatment energy of 114 kJ•kgsus −1 and 56 kJ•kgsus −1. For benchmarking, additional biomass was processed by high pressure homogenization. Homogeneity of the suspension prior to PEF-treatment influenced the protein/C-phycocyanin extraction efficiency. Stability of C-Phycocyanin durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A possible explanation could be that the phycobiliproteins do not only have to cross the cell membrane, but also dissociate from the thylakoid membrane. In this study, no phycocyanin was detected after 120 min incubation time, which is comparable to the results of Martinez et al Additionally, Akaberi et al [ 42 ] found a decrease in phycocyanin release and increase in incubation time (from 1 h to 5 h) when the biomass density was raised from 3.6 g/kg dw to 9.7 g/kg dw. It was concluded that release kinetics at high biomass concentration are significantly slower compared to low applied biomasses.…”
Section: Discussionsupporting
confidence: 91%
“…A possible explanation could be that the phycobiliproteins do not only have to cross the cell membrane, but also dissociate from the thylakoid membrane. In this study, no phycocyanin was detected after 120 min incubation time, which is comparable to the results of Martinez et al Additionally, Akaberi et al [ 42 ] found a decrease in phycocyanin release and increase in incubation time (from 1 h to 5 h) when the biomass density was raised from 3.6 g/kg dw to 9.7 g/kg dw. It was concluded that release kinetics at high biomass concentration are significantly slower compared to low applied biomasses.…”
Section: Discussionsupporting
confidence: 91%
“…Pulsed electric field was used for the production of PC from Arthrospira platensis. 1 µs pulses at an electric field strength of 40 kV•cm −1 were tested and the highest PC concentration was obtained [51]. Nostoc commune TUBT05 and Oscillatoria okeni TISTR8549 was investigated to obtain higher PC production.…”
Section: The Effects Of Reactants On Phycocyanin (Pc) Concentrations By Using Response Surface Methodologymentioning
confidence: 99%
“…Nonetheless, the poor efficacy of PEF to break the cell wall and release intracellular components of rigid cell walled microalgae does not necessarily imply that PEF will not be efficient on weak cell walled species (Safi et al 2017). For instance, by means of PEF, highly pure b-Pycoerythrin and C-Phycocyanin were successfully extracted from Porphyridium cruentum and Arthrospira platensis, respectively (Martínez et al 2019;Akaberi et al 2020).…”
Section: Pulsed Electric Fieldmentioning
confidence: 99%